Oral hygiene motivational talks for parents or guardians of children aged 5 to 8 years and its influence on the duration of composite resin restorations: a clinical study with a 24 months follow-up in Ecuador - Ana del Carmen Armas-Vega; Osmani Fabricio Guevara-Cabrera; Eduardo Antonio Bravo-Polo; Carlos Gustavo Martínez-Florencia; Valeria Elizabeth Banderas-Benítez; Joanna Tatith-Pereira; Fernando Borba-de Araujo (Universidad de Antioquia, 2018)
Introduction: tissue loss due to carious processes is usually resolved with restorations, requiring abundant patient collaboration in oral hygiene. The aim of the present study was to evaluate the effect of oral hygiene motivational talks addressed to parents or guardians of children aged 5 to 8 years on the duration of composite resins over 24 months. Methods: a prospective descriptive study was conducted in 31 children and their parents or guardians meeting the inclusion criteria. The parents and guardians were trained in oral hygiene techniques, and the participating children's cavitated teeth were restored with composite resin, providing dental cleaning devices every 6 months during the study period. Clinical evaluations were performed every 6 months during the study period, evaluating the deterioration of restorations and the presence of visible plaque (VPI) and gingival bleeding (GBI). The data obtained were submitted to ANOVA statistical analysis and Student t-test through the STATA software. Results: There was a close relationship between oral hygiene indexes (p = 0,2019 for VPI and p = 0,6243 for GBI) and the deterioration of restorations, especially those involving proximal sides. Survival analysis showed that failure is lower in the presence of nearby caries (42.9%), with p values of 0.0045 for the occlusal-distal surface and 0.0291 for the occlusal-mesial one. Conclusion: the oral hygiene motivational talks addressed to parents or guardians of participating children influence the durability of composite resins.